DEVELOPMENT OF A POWERPOINT-BASED GERITA MEDIA TO IMPROVE GRADE I STUDENTS’ LEARNING OUTCOMES - Fikriana Aulia Rakhmah; Deasylina da Ary (Universitas Labuhanbatu, 2026)
Purpose – This study aims to develop, assess the feasibility of, and test the effectiveness of the GERITA (Visual Stimuli in Dance Movement) PowerPoint-based learning medium to improve the learning outcomes.Methodology – This is a Research and Development (R&D) study using the ADDIE model with a pre-experimental one-group pretest-posttest design. The research subjects were 22 first-grade students at SD Negeri 2 Kertanegara, Purbalingga Regency. The research method used was a mixed-methods approach. Data were collected using test-based (pre-test and post-test) and non-test-based (interviews, questionnaires, and documentation) techniques, then analyzed using normality tests, paired-samples t-tests, and N-gain tests.Findings – The development of the GERITA media integrates visual, audio, and interactive navigation elements into a single, simple digital platform, while also applying an embodied learning approach that connects visual and audio stimuli with students' physical experiences. The results of the feasibility validation indicated that the GERITA media received a